What are Parents’ Perceptions of the Nature of Their Participation at the High School Level? - Lal, Rita; Adams, Pamela; Mombourquette, Carmen (Alberta Journal of Educational Research, 2021)
The purpose of this study was to gain insight from parents and guardians about their experiences of involvement in the education of their high school aged children. Data were gathered using interviews for nine randomly selected participants from an urban high school in Alberta, Canada. Thematic analysis identified the types of activities parents perceived to constitute participation, barriers encountered, and potential school structures to enhance future involvement. Findings revealed that parents considered volunteering, attending activities, academic support, school council, and providing feedback as valued types of participation. Barriers were classified as child-based challenges, school-based challenges, and parent-based limitations. Key words: secondary education, parent engagement, parent participation, educational administration, school leadership L'objectif de cette étude était d'obtenir des informations de la part des parents et des tuteurs sur leurs expériences de participation à l'éducation de leurs enfants en âge de fréquenter l'école secondaire. Les données ont été recueillies au moyen d'entretiens avec neuf participants choisis au hasard dans une école secondaire en milieu urbain en Alberta, au Canada. L'analyse thématique a permis d'identifier les types d'activités que les parents considèrent comme constituant une participation, les obstacles rencontrés et les structures scolaires potentielles pour améliorer la participation à l’avenir. Les résultats ont révélé que les parents considéraient le bénévolat, la participation aux activités, le soutien scolaire, le conseil d'école et le fait de fournir des commentaires comme des types de participation appréciés. Les obstacles ont été classés comme des défis liés à l'enfant, des défis liés à l'école et des limites liées aux parents. Mots-clés: enseignement secondaire, engagement des parents, participation des parents, administration de l'éducation, direction des écoles